POTENSI PRODUKSI HIJAUAN PADA PASTURA ALAMI DI PULAU SAMOSIR KABUPATEN SAMOSIR - Nevy D. Hanafi (Talenta Publisher, 2017)
Samosir island has potential ruminant livestock development include beef cattle, buffaloes, goatsand horses. This study aims to determine the potential of the forage production on natural pasturesin Samosir, Samosir regency. Research carried on in Samosir in July to October 2016. Assessmentof Forage Feed on pasture land in Samosir includes determining the locations of the study based onaltitude, sampling forages and forage calculate productivity. Location of the study amounted to 15points, at an altitude of 905-1200 meters above sea level there are nine (9) research sites thatSimbolon, Simanindo, Unjur, Garoga, Marlumba, Suhisuhi Dolok, Parbaba Dolok, Onan Runggu,Sabungan Nihuta. While at an altitude up 1200 m above sea level, there are 6 locations includingresearch Tanjungan, Sidihoni, Lintong Sunut, Desa Lumban Simbolon, Sipira 32, dan Sipira 33. Theresults showed that the fresh Production of highest at an altitude 905-1200 meters above sea levelwas 2.048,27 kg/ha/harvest, and production dry matter is 814,43 kg/ha/harvest. Temporarily themean production of fresh ingredients at an altitude up 1200 m above sea level is 1.696,1 kg/ha/harvestand production dry matter is 739,28 kg/ha/harvest. Conclusion altitude on pasture gives effect to theproduction of fresh and dry matter forage.